Hubungan status gizi dengan kejadian penularan tuberkulosis dalam keluarga di Desa Batusumur Kecamatan Manonjaya Kabupaten Tasikmalaya - Dewi, Candrawati Puspita; Raharjo, Mursid; Adi, Mateus Sakundarno (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Tuberculosis is the second infectious disease that causes the most deaths in the world according to WHO. Indonesia is a high TB burden country which currently ranks third in the world, with an incidence of 845.000 or 320/100.000 population with a mortality rate of 98.000 or 40/100.000 population and 3,6/100.000 TB-HIV population. The risk factor that can cause tuberculosis disease is malnutrition. The aim of the study was to determine the relationship between nutritional status and the incidence of tuberculosis transmission in the family. The purpose of this study was to determine the relationship between nutritional status and the incidence of tuberculosis. The research design used cross sectional study. The research was conducted in December 2023 in Batusumur Village, Manonjaya District, Tasikmalaya Regency. The research sample was 39 respondents of tuberculosis patients. Inclusion criteria: patients actively communicate and are easy to talk to, patients live with family members and are still in the initial phase of treatment in the first 2 months. The independent variable was nutritional status. The dependent variable was the incidence of pulmonary tuberculosis transmission in family members. The instrument was an observation sheet. Data were analyzed by chi square test using SPSS. This research applies the principles of confidentiality, useful information and scientific development. The results showed that there was a relationship between nutritional status (p=0,026) and the incidence of tuberculosis transmission in the family. The conclusion is that there is a relationship between nutritional status and the incidence of tuberculosis. Tuberculosis patients and their families can make preventive efforts to prevent tuberculosis transmission.